The Relation of Mixed Marketing with Patient Loyality in Syekh Yusuf Gowa General Hospital (Medico Legal Update, 2020)
It is important for hospitals to have the right marketing strategy, with marketing programs conductedcan improve the quality of service, with good service quality, it will be able to satisfy customers so thatcustomers will be loyal. This study aims to determine the relationship between the mixed marketing withpatient loyalty in the Syekh Yusuf Gowa Regional Hospital. This type of research is an observational studywith a cross sectional study approach. The population in this study were all inpatients who used servicesat the SyekhGowa Regional General Hospital in a amonth. The sampling method was done by accidentalsampling, which is 114 respondents. Data analysis in this research was carried out by testing hypothesesthrough the correlation test method. Bivariate analysis with correlation test shows that there is a relationshipbetween the mixed promotion (P = 0,000), mixed service provider (P = 0,000), mixed physical facility (P =0.012) and patient loyalty, but there is no relationship between the mixed process (P = 0.064) with patientloyalty. So, there is a relationship between the mixed marketing of promotion, mixed marketing of servicepresenters, mixed marketing of physical facilities and patient loyalty.